Intravoxel incoherent motion diffusion-weighted imaging and shear wave elastography for evaluating peritumoral liver fibrosis after transarterial chemoembolization in a VX2 rabbit liver tumor model - Cheng, Zhimei; Yang, Qin; He, Huizhou; Li, Ran; Li, Xueying; Jiang, Hongyu; Zhao, Xuya; Li, Junxiang; Wang, Lizhou; Zhou, Shi; Zhang, Shuai (Frontiers in Physiology, 2022)
In this study, we sought to evaluate changes in peritumoral fibrosis after transarterial chemoembolization (TACE) in a rabbit VX2 liver tumor model using intravoxel incoherent motion diffusion-weighted imaging (IVIM DWI) and ultrasound shear wave elastography (SWE). A total of 20 rabbits underwent implantation of VX2 tumor tissues in the left lobe of the liver. The rabbits were randomly divided into an experimental group (n = 10) or a control group (n = 10). Those in the experimental group were treated with an emulsion of lipiodol and pirarubicin through a microcatheter 2 to 3 weeks after implantation; those in the control group were treated with sterile water. Compared with the control group, the true diffusion coefficient (D) and pseudodiffusion coefficient (D*) values in liver tissues were significantly lower (P < 0.05 for all) and liver stiffness values (LSV) (10.58 ± 0.89 kPa) were higher in the experimental group (7.65 ± 0.86 kPa; P < 0.001). The median stage of liver fibrosis based on METAVIR scores was 1 (1, 1) in the control group and 2 (2, 3) in the experimental group (Z = 4.15, P < 0.001). D, D*, and LSV were significantly correlated with pathologic staining in the assessment of liver fibrosis (r = –0.54 P = 0.015; r = –0.50, P = 0.025; r = 0.91, P < 0.001; respectively). These data suggest that TACE aggravates liver injury and liver fibrosis, especially surrounding the tumor, in a rabbit VX2 liver tumor model. IVIM DWI and SWE can be used to evaluate the change in liver fibrosis.